Online monitoring system of respiration (Oxygen Transfer Rate) of microoganisms in aerobic fermentation / Rosmaria Abu Darim … [et al.] - Abu Darim, Rosmaria; Azizan, Amizon; Mohammad Din, Mohd Ibrahim; Tomijan, Mohd Hafis; Mohd Yusof, Nurul Fitri (Research Innovation Business Unit, 2014)
Facultative microorganisms can be grown either in aerobic or anaerobic system. Both conditions will end up with different metabolic pathways which may also be influenced by certain inhibitions or limitations. Substrate, oxygen or product limitations or inhibitions are some of the examples. For aerobic system, oxygen transfer rate (OTR), oxygen uptake rate (OUR) and respiration quotient (RQ) are significant parameters which must be investigated and monitored during fermentation. However, during screening, since most of the researchers run fermentation in shake flask in which online monitoring is highly lacking or ignored, it may lead to uncertain or unwanted screening strategies or metabolic pathways. Shake flask is the common bioreactor system prior to screening. Most problems which occur are due to oxygen limitation conditions in the shake flask before the large-scale fermentation is being conducted without being realized by the researcher. Some conditions which imitate or are created for any nearly anaerobic conditions are not fully defined or noticed since the OTR, OUR and RQ are not closely being monitored during shake flask fermentation. The metabolic pathways of the microorganisms may change due to the unwanted growth during fermentation. Above all, consequently, online monitoring system (real time data) for respirations of facultative microorganism during screenings prior to large scale fermentation must be established. In this setup, the oxygen and carbon dioxide concentration during fermentation are monitored real timely. The lag, exponential, stationary and death phases could be identified in normal shake flasks which are commonly used by all biological scientists in the laboratory. With this establishment, the problem of unknown screening strategies could be evaluated which would then optimize the unwanted cost of screening strategy for any product based fermentation in bio-processing industry. Most common bacteria which behave facultatively are Escherichia coli or any yeast such as Saccharomycess cerevisiea are investigated this setup. The design setup consists of shaking, growing and data collecting mechanisms. Screenings of microorganisms in the shake flasks are influenced by many parameters like temperature, shaking frequency, filling volume, inoculum size and age, shaking diameter, OTR and OUR are monitored and RQ can be analyzed from the data collected. Oxygen and carbon dioxide sensors must be implemented in the shake flask for the online monitoring of the fermentation. During any aerobic fermentation, oxygen is consumed and carbon dioxide is released in shake flask. Therefore, the oxygen and carbon dioxide sensors collect the real time data from the beginning until the end of the fermentation monitoring, the lag, exponential, stationary and death phase. The specific growth rate can be monitored during the exponential phase with this monitoring. The lag phase can be minimized with the change of certain parameters involved like filling volume and inoculums size. The higher filling volume will result in longer adaptation to fermentation resulting in longer lag phase. The younger the inoculums, the shorter the lag phase, resulting in abrupt exponential phase with higher specific growth rate of microorganisms. With the monitoring of the screening process, some costs incurred due to falsely grown microorganisms leading to false or lesser production rate can decrease.